Wait i’m confused on how this equation is modeled i’m sorry do you have a picture? i wanna be sure i answer this right.
Answer:
3*10^3
Step-by-step explanation:
4.8(10^9)/1.6(10^3)
we can split this equation into
4.8/1.6 * 10^9/10^3
= 3*10^3
Answer:
4
Step-by-step explanation:
![\lim_{n \to \ -\pi } (f(x) - g(x))\\\\ = \lim_{n \to \ -\pi } (3 - cos x)\\\\ = 3 - cos( - \pi) = 3 - cos(\pi)\\\\ = 3 - (-1) = 3 + 1 = 4](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5C%20-%5Cpi%20%7D%20%28f%28x%29%20-%20g%28x%29%29%5C%5C%5C%5C%20%3D%20%5Clim_%7Bn%20%5Cto%20%5C%20-%5Cpi%20%7D%20%283%20-%20cos%20x%29%5C%5C%5C%5C%20%20%3D%203%20-%20cos%28%20-%20%5Cpi%29%20%3D%203%20-%20cos%28%5Cpi%29%5C%5C%5C%5C%20%3D%203%20-%20%28-1%29%20%3D%203%20%2B%201%20%3D%204)
Answer:
a = 0
Step-by-step explanation:
=> 3(a+4)-5(a-2) = 22
Opening Brackets
=> 3a+12-5a+10 = 22
=> 3a-5a+12+10 = 22
=> -2a+22 = 22
Subtracting 22 to both sides
=> -2a = 0
Dividing both sides by -2
We get,
=> a = 0
Answer:
no these are not equivalent
Step-by-step explanation:
these aunt equivalent because 12+12 =24 and 3+3=6 not 7 or 28 so no ccx these are not equivalent